The Mediating Role of Circle of Friends and Flexing on FOMO and Israf in Gen Z’s Imitation Fashion Purchase Decisions - Ayu Ariska; Ida Farida; Hukmiah Husain (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2025)
Introduction: This study aims to analyze the mediating role of Circle of Friends and Flexing on the influence of Fear of Missing Out (FOMO) and Israf (excessive consumption) on purchasing decisions of imitation fashion products among Generation Z in Bone Regency. These social and psychological factors are known to be the main drivers of increased consumption of counterfeit goods. Methods: This research uses a quantitative approach with associative methods and Structural Equation Modeling-Partial Least Square (SEM-PLS) analysis techniques. Primary data were obtained through the distribution of online questionnaires to 230 respondents using a purposive sampling technique. The measurement instrument used a Likert scale of 1 to 5 and was tested for validity and reliability. Results: The t-value for the Circle of Friends variable on Purchase Decisions was 7.333 with a significance level of 0.000, and Flexing had a t-value of 3.235 with a significance of 0.001. Both were statistically significant. FOMO had a significant effect on Circle of Friends (t = 2.575; p = 0.010) and Flexing (t = 3.162; p = 0.002), but it did not directly affect Purchase Decisions. Meanwhile, Israf had a significant effect on Circle of Friends (t = 5.354; p = 0.000), Flexing (t = 4.914; p = 0.000), and Purchase Decisions (t = 2.606; p = 0.010). The indirect influence through both mediators was also proven significant. Conclusion and suggestion: The results of the study conclude that Circle of Friends and Flexing significantly mediate the influence of FOMO and Israf on purchasing decisions of imitation fashion products. These findings confirm the importance of social influence and self-imaging motivation in Generation Z's consumption behavior. It is recommended that education about authentic consumption and strengthening regulations against counterfeit goods be improved.